(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
While content knowledge and instructional skills are widely acknowledged as pillars of effective teaching, less attention is paid to the subtle and powerful influence of teacher role modeling. This study explores the role of teacher role modeling in shaping students’ perceptions of teaching effectiveness within a higher education institution in Uzbekistan. The research adopts a mixed-methods design to address the dual nature of the subject: the measurability of effectiveness and the interpretive nuance of role perception. Quantitative data were collected through structured questionnaires from 102 undergraduate students, complemented by qualitative responses to open-ended questions aimed at capturing student narratives and emotional impressions. Results indicate a statistically significant positive correlation between perceived role modeling and perceived teaching effectiveness, with students placing particular emphasis on behavioral consistency, ethical values, time discipline, and communication style. Qualitative findings further contextualize these preferences, revealing that students interpret role modeling through both academic professionalism and personal integrity. The study contributes to the evolving discourse on effective teaching by illuminating the social and psychological dimensions of the classroom dynamic. Practical implications are proposed for faculty development initiatives, institutional standards, and the broader agenda of improving educational quality in transitional academic systems.